Students’ Perceptions of the Episoden Application in Enhanching Speaking Skills - Azizka, Baiq Zara; Usuluddin, Usuluddin; Surayya, Siti Ayu; Wati, Laila (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates students’ perceptions of using the Episoden application to enhance English speaking skills at MA Manba’ul Bayan. Speaking is often considered the most challenging skill for EFL learners due to limited opportunities for authentic practice, lack of confidence, and vocabulary constraints. To address this, Episoden, a mobile-based platform that enables real-time video conversations with international speakers, was introduced as a supplementary learning tool. The research employed a qualitative descriptive design, with data collected through classroom observations, interviews, and field notes involving eleventh-grade students. Findings revealed that students initially experienced anxiety and hesitation when using the application, but gradually developed greater confidence, fluency, and motivation after repeated practice. The application provided authentic communicative experiences, supported intercultural interaction, and allowed learners to practice beyond the classroom at their own pace. Despite technical challenges such as unstable internet connections and difficulties understanding accents, students expressed positive attitudes toward Episoden and considered it an effective tool for improving their speaking skills. Overall, this study highlights the potential of Mobile Assisted Language Learning (MALL) applications like Episoden in fostering more meaningful and engaging speaking practice for EFL learners.